The Crystal Structure of (E)-5-Phenyl-N-(thiophen-2-ylmethylene)-1,3,4-thiadiazole-2-amine. - Demirtas, Gunes; Dege, Necmi; Sekerci, Memet; Servi, Suleyman; Dincer, Muharrem (Int Union Crystallography, 2009)
[Abstract Not Available]
Keywords: intramolecular interactions; intermolecular interactions; 1,3,4-thiadiazole